2014
DOI: 10.1080/00380768.2014.893537
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and genetic responses to boron deficiency inBrassica napus: A review

Abstract: Boron (B) is an essential microelement for the growth and development of plants, and B deficiency affects many biochemical and physiological processes. Brassica napus L. has a high demand for B and is extremely sensitive to B deficiency. Seed yields and oil quality of B. napus are often limited by the low availability of B in soils. Developing new cultivars of B. napus with high B efficiency is therefore required, which requires a greater understanding of responses to B deficiency. Significant genotypic differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 70 publications
1
25
1
1
Order By: Relevance
“…In contrast to most past studies, we observed no significant difference (Nable, 1988;Hayes and Reid, 2004;Roessner et al, 2006;Nable et al, 1990). Genotypic differences in response to low B availability have also been observed among Brassica napus L. varieties, wherein B-efficient genotypes with larger root systems can grow and yield normally as compared with intolerant genotypes (Zhang et al, 2014). Genotypic differences in response to low B availability have also been observed among Brassica napus L. varieties, wherein B-efficient genotypes with larger root systems can grow and yield normally as compared with intolerant genotypes (Zhang et al, 2014).…”
Section: Discussioncontrasting
confidence: 97%
“…In contrast to most past studies, we observed no significant difference (Nable, 1988;Hayes and Reid, 2004;Roessner et al, 2006;Nable et al, 1990). Genotypic differences in response to low B availability have also been observed among Brassica napus L. varieties, wherein B-efficient genotypes with larger root systems can grow and yield normally as compared with intolerant genotypes (Zhang et al, 2014). Genotypic differences in response to low B availability have also been observed among Brassica napus L. varieties, wherein B-efficient genotypes with larger root systems can grow and yield normally as compared with intolerant genotypes (Zhang et al, 2014).…”
Section: Discussioncontrasting
confidence: 97%
“…Brassica napus cv. Qingyou10 ( Q10 ) and Westar10 ( W10 ) are B‐efficient and B‐inefficient cultivars, respectively, and served to study physiological, molecular and genetic factors influencing B efficiency (Zhao et al ., ; Yang et al ., ; Zhang et al ., ,b, ; Yuan et al ., ; Zhou et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on sequence and expression analyses, BnaA03.NIP5;1b was subsequently suggested to be the responsible gene in the B efficiency loci of cv. Q10 (Xu et al ., , ; Zhao et al ., , ; Zhang et al ., ,b; Hua et al ., ,b). However, neither BnaA03.NIP5;1b nor BnaC02.NIP5;1a have been tested for their B permeability, although it is known that even highly homologous NIPs can possess different substrate selectivities (Zhao et al ., ; Mitani‐Ueno et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this response is in contrast to many other nutrient deficiencies, which either induce a shift in the shootto-root biomass ratio, such as under N, P, Mg or K deficiency, or strongly impair photosynthesis causing growth suppression indirectly via hampered assimilate provision (Hermans et al, 2006). Boron deficiency is of particular importance in Brassica species, which are highly sensitive to B deficiency (Bergmann, 1992;Herrera-Rodriguez et al, 2010;Zhang et al, 2014). In the present study, we employed rapeseed to determine which PH species change in association with the B nutritional status and are involved in B-dependent growth responses.…”
Section: Introductionmentioning
confidence: 99%